2013
DOI: 10.1101/cshperspect.a014308
|View full text |Cite
|
Sign up to set email alerts
|

Role of MYC in Medulloblastoma

Abstract: Since its discovery as an oncogene carried by the avian acute leukemia virus MC29 in myelocytomatosis (Roussel et al. 1979) and its cloning (Vennstrom et al. 1982), c-MYC (MYC), as well as its paralogs MYCN and MYCL1, has been shown to play essential roles in cycling progenitor cells born from proliferating zones during embryonic development, and in all proliferating cells after birth. MYC deletion induces cell-cycle exit or cell death, depending on the cell type and milieu, whereas MYC and MYCN amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 96 publications
5
112
0
Order By: Relevance
“…Our studies and those of others have shown that Myc can confer metastatic phenotypes in medulloblastoma (6)(7)(8). Although mechanisms of Myc-mediated transformation in medulloblastoma remain largely unknown, multiple lines of data suggest Mycdriven medulloblastoma are dependent on PI3K/AKT signaling (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and point to the PI3K/AKT axis as a critical downstream effector of Myc in group 3 medulloblastoma (7,16,17). Activation of PI3K/AKT signaling has been shown to promote various oncogenic phenotypes in medulloblastoma including enhanced tumor growth, metastasis, and chemoresistance (14,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 94%
“…Our studies and those of others have shown that Myc can confer metastatic phenotypes in medulloblastoma (6)(7)(8). Although mechanisms of Myc-mediated transformation in medulloblastoma remain largely unknown, multiple lines of data suggest Mycdriven medulloblastoma are dependent on PI3K/AKT signaling (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and point to the PI3K/AKT axis as a critical downstream effector of Myc in group 3 medulloblastoma (7,16,17). Activation of PI3K/AKT signaling has been shown to promote various oncogenic phenotypes in medulloblastoma including enhanced tumor growth, metastasis, and chemoresistance (14,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 94%
“…Among the pathways that heighten MYC expression and are frequently mutated in cancers are Wnt-b-catenin, Sonic hedgehog-Gli, and Notch. For reviews on the role of MYC family genes in neoplasia, see Huang and Weiss (2013), Kuzyk and Mai (2014), Roussel and Robinson (2013), Gabay et al (2014), and Schmitz et al (2014). Therapeutic approaches to cancer through inhibition of MYC activity are reviewed in Bradner (2014), Gabay et al (2014), and Cermelli et al (2014).…”
Section: Association Of Myc With Tumorigenesismentioning
confidence: 99%
“…Simply put, MYC is under extraordinarily tight regulation by the cell. A corollary of this is that defects in regulation can, and do, occur at many levels, leading to the increased abundance and inappropriate expression of MYC typical of many cancers (see Huang and Weiss 2013;Roussel and Robinson 2013;Gabay et al 2014;Schmitz et al 2014). Our increasing knowledge of key regulatory events has led, and will continue to lead, to therapeutic approaches aimed at subverting MYC production (Gustafson and Weiss 2010;Dawson et al 2011;Delmore et al 2011;Mertz et al 2011;Zuber et al 2011;Loven et al 2013;Puissant et al 2013;Bradner 2014).…”
Section: Myc As a Sensor And Effector Of Cellular Informationmentioning
confidence: 99%
“…While migrating through the Shh-rich EGL toward PCs, CGNPs exit the cell cycle and differentiate, demonstrating the exquisite balance between proliferation and differentiation that is required to coordinate CGNP clonal expansion and granule neuron generation. Overactive Shh signaling characterizes one of the four molecular subgroups of medulloblastoma, the most common malignant brain tumor in children, and occurs in ∌25-30% of cases, making this signaling pathway an attractive target for novel therapeutics (Roussel and Robinson, 2013;Taylor et al, 2012). Therefore, to further understand pathological conditions, it is crucial to investigate the cellular/molecular mechanisms that act during granule cell development to initiate differentiation in preference to proliferation in the presence of mitotic/morphogenetic signals.…”
Section: Introductionmentioning
confidence: 99%